PEMETAAN KEKUATAN & PRODUKTIVITAS PERGURUAN TINGGI DI INDONESIA BERBASIS PUBLIKASI ARTIKEL ILMIAH - Mahiswara, Kenindra; Refariansyah, Febizio; Oktaviani, Dea (Majalah Ilmiah UNIKOM, 2019)
As government policies that are already set, that permanent lecturer and postgraduate students must do the publication of scientific articles that are accredited or accepted in international journal, the Data used in this research is scientific articles from permanent lecturers and postgraduate students which is taken through the famous site i.e. Scopus. The purpose of this study is to see the productivity of permanent lecturer and postgraduate students from the University. The methods used for this research is the k-means clustering, stop-word removal, stemming. The results of this research is the cluster that has the highest citations per document and the productivity of the permanent lecturer and postgraduate students. This research is expected to look at whether the permanent lecturer and postgraduate students already obey policy from the Government. Key words: k-means clustering, stop-word removal, stemming